Crônicas de fã - Sales, Alaiane dos Santos (Universidade Federal do Tocantins, 2022)
The present work aims to present a series of episodes with journalistic chronicles, based on facts that happened in the career of the artist Lady Gaga, dating from 2017, which were reported by the Brazilian media. Using the fan's gaze as a parameter, the podcast, a format on the rise, appears with the aim of promoting the chronicle, especially for the young audience, so that it does not fall into oblivion, and to create a service aimed at the Pop Fan.